Contributing Factors and Evolution of Impulse Control Disorder in the Luxembourg Parkinson Cohort - Binck, Sylvia; Pauly, Claire; Vaillant, Michel; Hipp, Geraldine; Gantenbein, Manon; Krueger, Rejko; Diederich, Nico J (Frontiers in Neurology, 2020)
Background: To establish the frequency of impulse control disorder (ICD) in Parkinson’s disease (PD). Methods: Within the Luxembourg Parkinson’s Study, PD patients were evaluated for ICD presence (score ≥ 1 on MDS-UPDRS I item 1.6), use of dopamine agonists (DA) and other medications. Results: 470 patients were enrolled. Among 217 patients without DA use, 6.9% scored positive for ICD, versus 15.4% among 253 patients with DA use (p=0.005). The regression analysis showed that age at PD diagnosis had only a minor impact on ICD occurrence, while there was no influence by gender or comedications . The longitudinal study over two years in 156 patients demonstrated increasing ICD frequency in DA users (p = 0.005). Conclusion: This large and non-interventional study confirms that PD patients with DA treatment show higher frequency of ICD than patients without DA use. It newly demonstrates that ICD can develop independently from age, gender or comedications.